Analisis Kelayakan Anggaran Investasi Teknologi Informasi dengan Analisis Cost Benefit - Fajar Hertingkir; Deni Wardani (STIE Indonesia Banking School, 2017)
Analysis of costs and benefits is an instrument for assessing whether a project is feasible to be implemented or not. STIE IBS is currently developing a new system so that services to students can be better. Projects currently under consideration is a system of academic information system and internet connection. Both of these investment projects will be assessed each of its cost-benefit. The assessment results in the form of recommendations to the interested parties concerning which projects should be built first. This study uses cost-benefit analysis combined with analysis of cost budgeting. The implementation of this study begins by analyzing the existing projects in the information technology department to analyze the cost-benefit obtained from each of these projects, then do the calculations the difference between the benefits gained by the investment budget has been budgeted at the beginning. The analysis showed that the two investment projects in the budget it is worth the investment benefit, in other words, the technology field is greater than the costs. From both of those project, the procurement of Internet connection is recommended for doing first